Synergistic effects of quercetin and vitamin E on egg production, egg quality, and immunity in aging breeder hens - Felix Kwame Amevor (Elsevier, 2021)
ABSTRACT: Laying hens experience a rapid decline in egg production, egg quality, and immunity, usually at the end of the peak laying period. Quercetin, a known flavonoid, exerts biological activities, including phytoestrogenic, immunity, antibiotic, antioxidant, and anti-inflammatory properties. Vitamin E also shows egg production and immunoregulatory potential in animals. This study evaluated the capacity of dietary quercetin, vitamin E, and the combination of both, to promote egg production and egg quality, and to improve the immunity of aging breeder hens. We also elucidated how quercetin and vitamin E combination could synergistically affect egg production, egg quality, and immunity in aging breeder hens. A total of 400 Tianfu broiler breeders at the age of 52 wk were randomly allotted to 4 treatments with 4 replicates, 100 hens per treatment and 25 hens per replicate. They were fed diets containing quercetin at 0.4 g/kg, Vitamin E (200 mg/kg), quercetin and vitamin E (0.4 g/kg and 200 mg/kg), and a basal diet (control) for a period 10 wk. Daily feed intake and egg production rate were recorded, and weekly records were recorded on egg quality tests. At the end of the 10-wk experimental period, blood samples and immune organ (spleen) were collected from 2 birds per replicate, totaling 32 birds. Feed intake, immune organ index, serum cytokines, and immunoglobulins were evaluated, and the mRNA expression of genes related to immunity was determined from the spleen tissue. Generally, the results showed that separately or as a combination, supplemental quercetin and vitamin E significantly improved performance and egg quality (P < 0.05), and significantly increased serum immunoglobulins (IgA, IgM, and IgG) and cytokines (IFN-γ and IL-2) concentrations, as well as promoted immune organ development and index, and promoted the expression of splenic immune-related genes (IL-2 and INF-γ) (P < 0.05), compared with the control. It was confirmed in this study that the combination of quercetin and vitamin E exert synergistic effects on egg production, egg quality, and immune function in aging hens.